Positive Self-Talk Intervention to Decrease Stress in Parents of Children with Special Needs - Prilia Zulfatur Rohmah; Maulita Noor Aisha; Eny Purwandari; Diajeng Laily Hidayati (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2022)
The caregiving experience of parents of children with special needs (CSN) can be challenging and can lead to significant stress and negative impacts on mental health. To address this issue, a community service activity was implemented to provide positive self-talk training to 25 parents of CSN who are members of the Indonesian Special Family Forum (FORKESI) in South Sumatra. The training was conducted online using the Zoom Meeting platform and employed the Asset Based Community Development (ABCD) method. The results of the community service indicated that the average stress levels of the participants decreased after participating in the training. Additionally, participants reported feeling more grateful for the condition of their children, more accepting of their children's condition, and having more open minds. These findings suggest that positive self-talk training is an effective strategy for reducing stress in parents of children with special needs and may have broader implications for supporting caregivers in the community.